ADDRESSING SERVICE ACCESS BARRIERS FOR HOMELESS YOUTH: A CALL FOR COLLABORATION - Jeffrey L. PERRON (Journal of Urban and Regional Analysis, 2022)
Homeless youth are among the most vulnerable individuals in North American society. The day-to-day stressors they face while living on the streets pose a great threat to their mental and physical health. A number of barriers that youth face in accessing care have been identified in the literature. This discussion article highlights work that has been done to apply geographic theory to issues of service access among homeless youth. To date, most such work has been theoretical in nature, with collaborations between geographers and homeless youth researchers to make applied recommendations for the location of services. Urban geographers and homeless youth researchers are implored to collaborate in order to make recommendations that will increase the access to service, particularly for rural homeless youth.